2014
DOI: 10.17305/bjbms.2014.4.175
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in body height in Balkan populations from 1945 to 1995

Abstract: The aim of this study was to look for any secular trend in the stature of Balkan populations from the time of World War II (1939-1945) to the Balkans War (1991-1995). The research was based on the examination of exhumed skeletons of 202 men killed in World War II in the area of the Republic of Slovenia, and 243 men killed in the Bosnian War in Bosnia and Herzegovina. The length measurements of the right and left humerus, femur, tibia and fibula were taken. Since the results revealed no significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Populations around the world display different secular trends in height in the past century on the basis of their socioeconomic, life style, and rescue from the wars . The Sardinian population after World War II experienced a dramatic economic and social advancement .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations around the world display different secular trends in height in the past century on the basis of their socioeconomic, life style, and rescue from the wars . The Sardinian population after World War II experienced a dramatic economic and social advancement .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increase in average height spanning over a century (secular trend) makes difficult to draw definite conclusions about the role of H. pylori infection and growth [34]. Populations around the world display different secular trends in height in the past century on the basis of their socioeconomic, life style, and rescue from the wars [35][36][37][38][39]. The Sardinian population after World War II experienced a dramatic economic and social advancement [22].…”
Section: Birth Cohortsmentioning
confidence: 99%
“…The key objective in physical anthropology is to document the vast range of human variability of past and present populations, and to investigate the evolutionary and environmental forces responsible for that variation [26]. Table 1 showed mean values of both the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Such changes have been documented in the stature. A secular trend in increase in height has been observed in developed countries since the late 19th century, mainly due to improvement in nutritional status as a result of ISSN: 2472-3800 socioeconomic development [24][25][26]. Mamidi et al [25], analyzed secular trend in height in a very large sample from different states of India and reported that, the increments in height for men and women were 0.50 cm per decade (p < 0.001) and 0.22 cm per decade (p < 0.001), respectively.…”
Section: Introductionmentioning
confidence: 99%